PENERAPAN MODEL PBL UNTUK MENINGKATKAN HASIL BELAJAR KELAS V PADA MATERI PENYAJIAN DATA DI SDN 1 KEBONDALEM LOR - Budiyono, Sri; Sri Windarti; Saputri, Cahya Novia; Astuti, Dwi Aprilia; Diani, Dwi Putri; Kusumaningtyas, Dyah Ayu; Puspa, Edelweis Mustika; Fauzan Wiranto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to improve the mathematics learning outcomes of data presentation material for class V-A students of SDN 1 Kebondalem Lor in the 2025/2026 academic year by applying the Problem Based Learning (PBL) model. This study is a Classroom Action Research (CAR) conducted in two cycles. The planning, implementation, observation, and reflection stages are part of each cycle. 19 students became the research subjects. Tests, observations, and documentation were used to collect data. Data were reviewed qualitatively and quantitatively. The results of the study indicate that the Problem Based Learning (PBL) model can improve student learning achievement. The average class score in cycle I was 69 and learning completeness was 57.9% (11 students completed). In cycle II, the average score increased to 89 and learning completeness was 84.2% (16 students completed). In the second cycle, teacher activity increased from 86.6% in the first cycle to 95.2%. The results of the study showed that fifth-grade students at SDN 1 Kebondalem Lor performed better in mathematics on data presentation after implementing the Problem-Based Learning (PBL) model.